Asesmen Kebutuhan Spiritual Pasien Penyakit Ginjal Kronik Yang Menjalani Hemodialisa Dengan Instrumen APSN dan SPNQ - Himawan, Fatchurozak; Anggorowati, Anggorowati; Chasani, Shofa (Journal of Holistic Nursing Science, 2019)
Patients with chronic kidney disease (CKD) undergoing haemodialysis require fulfilment of physical, psychological and spiritual needs. In the effort to meet the spiritual needs, it is necessary to do an appropriate spiritual needs assessment of the patients. Assessing a Patient’s Spiritual Needs (APSN) and Spiritual Needs Questionnaire Scale (SpNQ) are such available instruments for use in spiritual assessment. This study aimed to determine the spiritual needs of patients with chronic kidney disease undergoing haemodialysis using the APSN and SpNQ instruments. This study used a quantitative observation with a cross-sectional design. The samples were 104 patients undergoing haemodialysis for more than three months at Kardinah Hospital and RSUI Harapan Anda Kota Tegal. The results showed that the need of prayers was the highest spiritual needs in APSN in the dimension ‘divine’ as reported by 80 respondents (76.92%). Meanwhile, in SpNQ, the dimension of religiosity was rated the highest with 98 respondents (94.23%). Patients with CKD had spiritual needs in all dimensions both in APSN and SpNQ. The result of chi-square test showed a p-value of 0.170, indicating that there was no difference in the assessment of spiritual needs of patients using the APSN and SpNQ instruments. The APSN and SpNQ instruments could be further considered as alternative instruments to assess the spiritual needs of patients with CKD undergoing haemodialysis.